2008
DOI: 10.1088/0264-9381/25/15/154001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of winding cosmic wall lattices with X type junctions

Abstract: Abstract. This work confirms the stability of a class of domain wall lattice models that can produce accelerated cosmological expansion, with pressure to density ratio w = −1/3 at early times, and with w = −2/3 at late times when the lattice scale becomes large compared to the wall thickness. For walls of tension T I , the relevant X type junctions could be unstable (for a sufficiently acute intersection angle α) against separation into a pair of Y type junctions joined by a compound wall, only if the tension … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Carter's pentahedral model has a potential given by [10,13] where Φ = |Φ| e iφ , Ψ = |Ψ| e iψ , 0 < < 1, V = V 0 , θ = 2φ + ψ and χ = 2ψ − φ. The potential has five minima with V = 0 satisfying cos θ = cos χ = −1 and |Φ| 2 = |Ψ| 2 = 1/(1 − ).…”
Section: Consider the Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carter's pentahedral model has a potential given by [10,13] where Φ = |Φ| e iφ , Ψ = |Ψ| e iψ , 0 < < 1, V = V 0 , θ = 2φ + ψ and χ = 2ψ − φ. The potential has five minima with V = 0 satisfying cos θ = cos χ = −1 and |Φ| 2 = |Ψ| 2 = 1/(1 − ).…”
Section: Consider the Actionmentioning
confidence: 99%
“…Carter's pentahedral model [10,13] has been constructed as an example of a model having an odd number of vacuum configurations giving rise to an even type system through the formation of X-type junctions. However, in [5,6] the claim that Carter's pentahedral model would form X-type junctions has been challenged and it was argued that Y-type junctions would be formed instead.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the collisions of Nambu-Goto strings with junctions at which three strings meet have shown that the exchange to form junctions cannot occur if the strings meet with very large relative velocity. For the case of non-Abelian strings, rather than passing through one another they become stuck in an X configuration [34,36], in each case the constraint depending on the angle at which the strings meet, on their relative velocity, and on the ratios of the string tensions. Calculations of the average speed at which a junction moves along each of the three strings from which it is formed yield results consistent with the observation that junction dynamics may be such as to preferentially remove the heavy strings from the network leaving a network of predominantly light strings.…”
Section: Introductionmentioning
confidence: 99%
“…We use the energy density fractions as weight factors in the estimate of the Hubble damping term which needs to be added to Eq. (7). The equation describing the evolution of the characteristic velocity of the network then becomes…”
Section: -Dimensional the Energy Per Unit Length Of This Configuratmentioning
confidence: 99%